Long-Term Profiles of Bullying Victims and Aggressors: A Retrospective Study - Valera-Pozo, Mario; Flexas, Albert; Servera, Mateu; Aguilar-Mediavilla, Eva; Adrover-Roig, Daniel (Frontiers in Psychology, 2021)
Bullying is a widespread and worrying phenomenon, related to many different personal, behavioral, and social variables which can modulate it and its outcomes, also in the long term. These relationships are usually studied in children and adolescents, but less often in adults who have suffered or perpetrated bullying in the past. The present work explored the long-term characteristics of bullying victims and aggressors using a retrospective design. A sample of 138 adults of different ages completed an on-line protocol that included measures of bullying and victimization, substance use, sensitivity to reward and punishment, social skills, antisocial behavior, emotional regulation strategies, depression, anxiety, stress, self-esteem, and risk of suicide. The sample was divided into three groups (victims, aggressors, and controls) based on their responses to bullying-related questions. A set of Multiple Analyses of Variance with group as a fixed factor was carried out for each dependent variable. Victims and aggressors did not significantly differ in their self-reported substance consumption. Victims showed higher global depression, anxiety and stress in the past than aggressors (M = 34.66, SD = 11.74; aggressors: M = 19.70, SD = 16.53), higher emotional lack of control (M = 23.97, SD = 10.62; controls: M = 17.11, SD = 7.95) and rejection (M = 21.72, SD = 7.24; controls: M = 16.33, SD = 5.67), lower self-esteem (M = 27.72, SD = 6.70; controls: M = 31.60, SD = 6.60), and a larger frequency of suicidal thoughts (in the past) than controls. Aggressors showed higher sensitivity to reward (M = 12.03, SD = 3.66; controls: M = 8.42, SD = 3.92), larger communicational and relational skills (M = 22.10, SD = 7.20; controls: M = 17.96, SD = 7.16), and lower emotional sensitivity (M = 14.80, SD = 4.10; controls: M = 16.76, SD = 2.21). Accordingly, the logistic regression analysis identified sensitivity to reward and low psychological adjustment as the main predictors of the aggressor and victim profiles, respectively. The present results are discussed considering the extant literature on bullying and may help to improve prevention programs for this relevant social scourge.